SEMARANG JAVANESE ARTS CENTER IN SEMARANG WITH BEHAVIORAL ARCHITECTURE APPROACH - Annisa Sesa Qutrunnada (Canopy: Journal of Architecture, 2023)
Semarang City is one of the cities on the island of Java that also serves as the capital of Central Java Province. As a Javanese city, Semarang has its traditions, culture, and unique Javanese art with its charm. The Javanese art in Semarang is greatly influenced by hybrid culture factors, where the art has undergone many cultural acculturations throughout the city's history. Unfortunately, many of these arts are not well spotlighted due to a lack of activities to showcase them (events) and the limited spaces available to accommodate various Javanese art activities in Semarang. This has caused Javanese art in Semarang to experience a decline to the point where it is difficult to find information about these arts and a decrease in the art community itself. Additionally, globalization has affected the environment in which these arts develop. Generational differences and environmental changes have led to different behaviors in responding to Javanese art as a traditional art form in Semarang. Given this background, planning, and designing the Semarang Center for Javanese Art Building in Semarang is needed to accommodate Javanese art activities and provide information related to these arts. The approach that will be applied in the planning and design of the Semarang Center for Javanese Art Building is a behavioral architecture approach. This approach will study the behavioral patterns of the community in the context of Javanese art, both as artists and art enthusiasts, with a contemporary orientation. Therefore, the design output will be able to meet the current perception of the community.